Anthropomorphic or non-anthropomorphic? Effects of biological sex in observation of actions in a digital human model and a gantry robot model - Abel, Miriam; Kuz, Sinem; Patel, Harshal Jayeshkumar; Petruck, Henning; Klann, Juliane; Schlick, Christopher M.; Schüppen, André; Pellicano, Antonello; Binkofski, Ferdinand C. (Frontiers in Neurorobotics, 2022)
Robots are ever more relevant for everyday life, such as healthcare or rehabilitation, as well as for modern industrial environment. One important issue in this context is the way we perceive robots and their actions. From our previous study evidence exists that sex can affect the way people perceive certain robot’s actions (Abel et al., 2020). In our fMRI study, we analyzed brain activations of female and male participants while they observed anthropomorphic and robotic movements performed by a human or a robot model. While lying in the scanner, participants rated the perceived level of anthropomorphic and robotic likeness of movements in the two models. The observation of the human model and the anthropomorphic movements similarly activated the biological motion coding areas in posterior temporal and parietal areas. The observation of the robot model activated predominantly areas of the ventral stream, whereas the observation of robotic movements activated predominantly the primary and higher order motor areas. To note, this later activation originated mainly from female participants, whereas male participants activated, in both robot model and robotic movements contrasts, areas in the posterior parietal cortex. Accordingly, the general contrast of sex suggests that males tend to use the ventro-dorsal stream most plausibly to rely on available previous knowledge to analyze the movements; whereas female participants use the dorso-dorsal and the ventral streams to analyze online the differences between the movement types and between the different models. The study is a first step toward the understanding of sex differences in the processing of anthropomorphic and robotic movements.